Core competencies of small and medium-sized enterprises in the medical technology industry - Peissker, Nadine (My University, 2013)
The concept of core competencies has been increasingly studied in the last two decades, focusing mainly on multinational corporations. This study outlines the concept of core competencies in relation to the dynamic capabilities and the resource-based view and applies it to small and medium-sized enterprises (SMEs). The purpose of this study is to examine how core competencies assist SMEs to achieve a sustainable competitive advantage. The theoretical framework of this thesis is based on an extensive literature review of theories and concepts of strategic management, previous literature on SMEs and Hidden Champions. The theoretical findings are applied to four German SMEs, including two Hidden Champions, operating in the medical technology industry. The empirical part of this thesis focuses on what competencies the case companies possess and to what extent they create their firm’s sustainable competitive advantage. The main objective is to analyse the linkages between resources, capabilities and core competencies. The qualitative data is collected through a combination of interviews and questionnaires with three chief executive officers and one manager as well as medical journals, brochures and other organisational documents provided by the case companies. The empirical findings indicate that resources, capabilities and competencies are closely intertwined and that these internal factors strongly contribute to build and maintain the respective core competence. Innovativeness in product development within the case companies is considered as one of the most crucial competencies in the medical technology industry. However, Hidden Champions focus more on innovative activities and on the active involvement in national and international standardisation bodies than the other two SMEs do. This study does not only provide some theoretical contributions to existing literature but also offers several managerial implications for SMEs.
Keywords: Small and medium-sized enterprises; Hidden Champions; core competencies; sustainable competitive advantage; medical technology industry; fi=Markkinointi|en=Marketing|; fi=Master's Degree Programme in International Business|